Do we share the same view? Validating the shared mental models in team sports questionnaire - Raue, C.; Dreiskaemper, D.; Strauss, B. (Perceptual and Motor Skills, 2021)
Shared mental models (SMMs) can exert a positive influence on team sports perfor-mance because team members with SMMs share similar tasks and team-relatedknowledge. There is currently insufficient sports research on SMMs because the underlying theory has not been adapted adequately to the sports context, and different SMMs measurement instruments have been used in past studies. In the present study we aimed to externally validate and determine the construct validity of the "Shared Mental Models in Team Sports Questionnaire" (SMMTSQ). Moreover,we critically examined the theoretical foundation for this instrument. Participants were 476 active team athletes from various sports. While confirmatory factor analysis did not support the SMMTSQ`s hierarchical model, its 13 subfactors showed agood model fit in an explorative correlative approach, and the model showed good internal consistency and item-total correlations. Thus, the instrument`s subfactors can be applied individually, even while there are remaining questions as to whetherother questionnaires of this kind are an appropriate means of measuring SMMs in sport.